2015
DOI: 10.1016/j.jtbi.2014.10.012
|View full text |Cite|
|
Sign up to set email alerts
|

Oxygen as a critical determinant of bone fracture healing—A multiscale model

Abstract: Highlights The influence of oxygen was incorporated in a multiscale model of fracture healing.  The results of the oxygen model were compared with experimental observations.  An extensive sensitivity analysis of the oxygen model indicated its robustness.  Adequate spatiotemporal oxygen patterns appear to be critical for bone healing. Keywordsoxygen -angiogenesis -fracture healing -multiscale model -non-union AbstractA timely restoration of the ruptured blood vessel network in order to deliver oxygen and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 88 publications
0
71
0
Order By: Relevance
“…During endochondral ossification in particular, the cartilaginous matrix is penetrated by a vascular network before transforming into osseous tissue (Einhorn, 1998). Several studies have demonstrated that deficient angiogenesis leads to healing impairment (Carlier et al, 2015b, Kanczler and Oreffo, 2008, Saran et al, 2014, Tomlinson and Silva, 2013). Moreover, angiogenesis is a key factor for bone remodeling, because it provides the appropriate conditions for osteoblastic and osteoclastic activities (Kanczler and Oreffo, 2008, Saran et al, 2014, Claes et al, 2002).…”
Section: Angiogenesis and Vascularity Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…During endochondral ossification in particular, the cartilaginous matrix is penetrated by a vascular network before transforming into osseous tissue (Einhorn, 1998). Several studies have demonstrated that deficient angiogenesis leads to healing impairment (Carlier et al, 2015b, Kanczler and Oreffo, 2008, Saran et al, 2014, Tomlinson and Silva, 2013). Moreover, angiogenesis is a key factor for bone remodeling, because it provides the appropriate conditions for osteoblastic and osteoclastic activities (Kanczler and Oreffo, 2008, Saran et al, 2014, Claes et al, 2002).…”
Section: Angiogenesis and Vascularity Networkmentioning
confidence: 99%
“…Moreover, angiogenesis is a key factor for bone remodeling, because it provides the appropriate conditions for osteoblastic and osteoclastic activities (Kanczler and Oreffo, 2008, Saran et al, 2014, Claes et al, 2002). The endothelial cell plays a critical role in cell migration and transformation, secretion of growth factors, cell signaling, and other biological processes (Carlier et al, 2015b, Hankenson et al, 2015, Mayr-wohlfart et al, 2002). …”
Section: Angiogenesis and Vascularity Networkmentioning
confidence: 99%
“…Normal Fracture Healing Initially, it was assumed that vessels could only grow into the callus from the periosteum of the cortical bone (Burke and Kelly, 2012;Burke et al, 2013;Geris et al, 2008;Chen et al, 2009;Carlier et al, 2015). 3 % of the lattice points on this edge contained active vessels.…”
Section: Simulationsmentioning
confidence: 99%
“…As part of this study, our previous model of angiogenesis was updated to include a feature whereby blood vessels had to form a closed loop before they were considered active 32 . The benefit of this updated algorithm was that it made the model more physiologically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…If two vessels crossed the same path, anastomosis occurred and the two vessels fused together. As an extension of our previous model, and similar to the method described by Carlier et al 32 , it was assumed that blood and nutrients could only flow through vessels which had formed a closed loop. Based on this, the ECs which made up a blood vessel were considered inactive until anastomosis had occurred.…”
Section: Angiogenesismentioning
confidence: 99%